Compact dual-band microstrip bandpass filters using composite cross and open/short-circuited E-shaped resonators - Zhang, Runqi (2013)
In this paper, a class of new dual-band microstrip bandpass filters (BPFs) using composite cross and open/short-circuited E-shaped resonators is proposed. With the choice of the open- or short-circuited E-shaped resonator, the dual-band filter can be designed with different number of transmission poles in each passband. A transversal coupling scheme is used to analyze and design the proposed dual-band BPFs. Finally, two filters are analyzed, designed and tested to verify the proposed composite structure.